(untitled) (Medico Legal Update, 2021)
The purpose of this study is to establish reliability of estimating stature from the foot dimensions in South Indian population. Volunteers aged above 18 years were recruited for the study and measured using standard measuring using standardized measuring equipment. Anthropometric measurements taken include stature,foot length, foot breath, navicular height and malleolar heights. Correlations,regression formula and linear regression equations derived for both male and female showed positive correlation coefficient between stature and foot dimensions. To conclude foot dimensions were correlated with stature and can be a better predictor of stature.